MENANAM NILAI ISLAM SEJAK DINI: PERAN KUNCI ORANG TUA DALAM PENDIDIKAN ANAK USIA 7-12 TAHUN - Karina Lusiana; Hana Nur Hafidhah; Dahlia Raviyanti; Masrofah Tri Nurhidayati; Nabillah Khairunnisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the role of parents in Islamic education for children within the context of contemporary Muslim families. Using a literature review method based on various scholarly articles, the research found that Islamic education in the family significantly influences the development of children's character, moral values, and spirituality. Role modeling, habit formation, and effective communication are the main approaches applied by parents to nurture noble character from an early age. The findings also show that active involvement of both parents, strict digital supervision, and support from the local Islamic community are key supporting factors in creating an Islamic home environment. Islamic education at home has proven to have a mutually positive impact on children's development and the enhancement of parents' spiritual quality.